P03.01 Age of friends and norms about sexual behaviour are associated with hiv and hsv-2 status amongst young south african women in the hptn 068 study. (13th September 2015) - Fearon, E; Wiggins, R; Pettifor, AE; MacPhail, C; Kahn, K; Selin, A; Gomez-Olive, FX; Piwowar-Manning, E; Laeyendecker, O; Hargreaves, JR
Abstract : Introduction: Friends can be an important influence on HIV and sexual health via connexions to sexual partners, influential sexual behaviour norms, or provision of social support. In this study from rural South Africa, we examined associations between the characteristics of young women's friendships and their risk of Herpes Simplex Virus Type 2 (HSV-2) and HIV infection. Methods: In 2011–2012, we tested 2325 13–20 year-old young women participating in the HPTN 068 study baseline for HIV and HSV-2 and we collected descriptions of 5 friendships. We used logistic regression to analyse associations between HIV and HSV-2 and generated friendship net summary measures of the 5 friends' socio-demographic characteristics and the number of friends perceived to have had sex. We excluded those HIV positive and reporting never having had sex from the HIV analyses, as likely perinatal infections (n = 37). Results: Adjusted for participant and friendship net socio-demographic characteristics, each additional friend at least one year older than the participant was associated with raised odds of HIV (adjusted Odds Ratio = 1.45, 95% Confidence Interval 1.09–1.93, p = 0.014) and HSV-2 (aOR = 1.45, 95% CI 1.22–1.73, p < 0.001). Each additional friend perceived to have ever had sex also raised the odds of HIV (aOR = 1.32, 95% CI 1.04–1.68, p = 0.020) and HSV-2 (aOR = 1.21, 95% CI 1.06–1.38, p = 0.005). Conclusion: We found evidence that the ages of young women's friends and her perceptions of their sexual behaviour increase her risk for HSV-2 and HIV infection. While further longitudinal research would assist in disentangling causal relationships, the extent to which policies or programmes influence age-mixing and young people's normative environments, for example in school classes and youth groups, should be examined. Disclosure of interest statement: E Fearon was supported by a Bloomsbury Colleges and London International Development Centre PhD Studentship. The HPTN 068 trial is part of the HIV Prevention Trials Network and funded by the National Institutes of Health, United States.